2020
DOI: 10.3390/su12104003
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Psychological Effects of Walking in Urban Parks and Its Imagery in Different Seasons in Middle-Aged and Older Adults: Evidence from Matsudo City, Japan

Abstract: The benefits of park therapy have been investigated in young adults, but rarely for middle-aged and older adults. This study evaluates the physiological and psychological effects of walking in urban parks and park therapy images in winter, spring, and early summer. The experiments were implemented in two walking courses in the urban park in Japan and involved 12 middle-aged and older adults. Participants walked on walking courses in an urban park and city street for 11–15 min. Their heart rate and blood pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 43 publications
0
29
0
1
Order By: Relevance
“…In the published literature, the benefits of green walking in lowering blood pressure and improving psychological outcomes have been recorded [ 12 , 13 , 61 ]. Our findings of daytime green walking have reconfirmed the effects of lowering blood pressure and improving moods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the published literature, the benefits of green walking in lowering blood pressure and improving psychological outcomes have been recorded [ 12 , 13 , 61 ]. Our findings of daytime green walking have reconfirmed the effects of lowering blood pressure and improving moods.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, green environments have been widely recognized to be more advantageous to human health than urban environments [ 67 , 68 ]. Pratiwi, et al [ 12 ] have found greater improvements in blood pressure (SBP and DBP) and psychological parameters (POMS-TMD and STAI) after walking in an urban park than walking in the city. Likewise, similar results were also reported in other walking studies [ 49 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence shows that nature exposure can prevent and treat diseases that result from urban stressors, including air pollution, noise, and crowding [ 1 , 2 , 3 ]. Therefore, urban dwellers today are encouraged to visit urban green spaces such as urban forests and parks to improve their health conditions [ 4 , 5 ]. However, though urban greening has been advocated and promoted in recent decades, there is still a considerable part of the population who live in highly urbanized areas and have limited access to nature.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, psychological responses to walking through green space showed significantly correlation with trait anxiety levels [6]. Walking in parks leads to physiological, psychological relaxation, and varied landscape appreciation of mid-aged and old people [7]. Adolescent girls live near more parks with amenities that are conducive to walking and with active features, engage in more moderate or vigorous physical activity than those with fewer parks [8].…”
Section: Introductionmentioning
confidence: 99%